THE INTERPLAY OF SUPPLY NETWORK STRUCTURE AND FOOD SAFETY COMPLIANCE IN MALAYSIAN SMALL FOOD ENTERPRISES - Mohamad Zahari, Mohd Hafiz; Wahab, Samsudin (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study explores the relationship between supply chain management and sustainable business performance among small food service enterprises in Malaysia, emphasizing the mediating role of food safety compliance. Given the increasing regulatory demands and operational challenges faced by small food businesses, this study offers timely insights. Using SmartPLS and responses from 50 business owners and managers, the findings reveal that supply network factors such as transparency, flexibility, and integrity positively influence food safety adherence, which in turn supports long-term business viability. However, a direct link between supply network structure and sustainable outcomes was not observed, underscoring the mediating role of food safety compliance. The study also includes case-based insights to illustrate real-world challenges in food safety and supply chain practices. Due to the small sample size, generalizability is limited. The study contributes to both theory and practice by contextualizing performance factors in a regulated, resource-constrained environment.